Thermomechanics of Composite Structures under High Temperatures - Dimitrienko, Yu. I.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This pioneering book presents new models for the thermomechanical behavior of composite materials and structures taking into account internal physico-chemical transformations such as thermodecomposition, sublimation and melting at high temperatures (up to 3000 K). It is of great importance for the design of new thermostable materials and for the investigation of reliability and fire safety of composite structures. It also supports the investigation of interaction of composites with laser irradiation and the design of heat-shield systems. Structural methods are presented for calculating the effective mechanical and thermal properties of matrices, fibres and unidirectional, reinforced by dispersed particles and textile composites, in terms of properties of their constituent phases. Useful calculation methods are developed for characteristics such as the rate of thermomechanical erosion of composites under high-speed flow and the heat deformation of composites with account of chemical shrinkage. The author expansively compares modeling results with experimental data, and readers will find unique experimental results on mechanical and thermal properties of composites under temperatures up to 3000 K. Chapters show how the behavior of composite shells under high temperatures is simulated by the finite-element method and so cylindrical and axisymmetric composite shells and composite plates are investigated under local high-temperature heating. The book will be of interest to researchers and to engineers designing composite structures, and invaluable to materials scientists developing advanced performance thermostable materials.
Introduction -- Basic Notation -- 1 High-Temperature Environment and Composite Materials -- 2 General Equations of Multiphase Continuum Mechanics for Ablative Composites -- 3 Mathematical Model of Ablative Composites -- 4 Behavior of Matrices at High Temperatures -- 5 Reinforcing Fibres under High Temperatures -- 6 Unidirectional Composites under High Temperatures -- 7 Textile Ablative Composites Materials -- 8 Composites Reinforced by Dispersed Particles -- 9 Phenomena in Composite Materials Caused by Gradient Heating -- 10 Linear Ablation of Composites -- 11 Thermal Stresses in Composite Structures under High Temperatures -- 12 Mechanics of Composite Thin-Walled Shells under High Temperatures -- 13 Finite-Element Method for Modeling of Thermomechanical Phenomena in Composite Shells under High Temperatures -- 14 Methods of Experimental Investigation of High-Temperature Properties of Composite Materials.
Keywords: Mechanics, Applied; Solids; Thermodynamics; Ceramic materials; Numerical analysis; Condensed matter; Solid Mechanics; Thermodynamics; Ceramics; Numerical Analysis; Phase Transitions and Multiphase Systems